Penyuluhan Kesehatan Di Desa Sikayu Menuju Masyarakat Sadar Perilaku Hidup Bersih Dan Sehat (PHBS) Melalui Kuliah Kerja Nyata Dalam Rangka Mencegah Stunting Desa Sikayu Kecamatan Buayan Kabupaten Kebumen - Ajeng Puspo Aji; Anisa Putri Arianti; Amelia Amelia; April Ningsih (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Real Work Lecture is a community service activity carried out by students in Sikayu village which starts from 23 October – 11 November. KKN activities have three activity elements, namely education, MSMEs, and community service. KKN activities in Sikayu village will carry out socialization on PHBS, stunting and family planning. In this activity, PMT was also provided for the activity participants who came. All activities were successfully carried out with good results without any significant obstacles.